Seventeenth National Conference on Laser Technology and Optoelectronics 2022
DOI: 10.1117/12.2656510
|View full text |Cite
|
Sign up to set email alerts
|

High power linearly polarized narrow linewidth fiber laser

Abstract: Spectral beam combining technology based on diffraction grating is an effective method to obtain tens of thousands of watts or even hundreds of thousands of watts of high-power and high beam quality laser. The high power linearly polarized narrow linewidth fiber laser is an ideal sub-beam source in spectral beam combining systems. Limited by stimulated brillouin scattering and mode instability, the power increase of narrow linewidth lasers has been limited, especially in linear polarization systems. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The narrower the linewidth, the better the coherence. From a simple linear fitting of five groups of power and linewidth data points [9] in the research progress of 1064 nm fiber lasers, the results are shown in Figure 6 (the fitting only describes the rough relationship between laser power and coherence. In reality, it is not an ideal linear relationship.…”
Section: Analysis Of Influencing Factors Of Coherence On Remote Appli...mentioning
confidence: 99%
See 4 more Smart Citations
“…The narrower the linewidth, the better the coherence. From a simple linear fitting of five groups of power and linewidth data points [9] in the research progress of 1064 nm fiber lasers, the results are shown in Figure 6 (the fitting only describes the rough relationship between laser power and coherence. In reality, it is not an ideal linear relationship.…”
Section: Analysis Of Influencing Factors Of Coherence On Remote Appli...mentioning
confidence: 99%
“…In addition, because the power required for remote target detection has reached the order of kilowatts (kW) or even gigawatts (GW), which is much higher than the power level that can be achieved in China at present, the laser will also produce nonlinear effects while achieving high power. For example, SBS (stimulated Brillouin scattering) is more likely to occur when the linewidth is narrow, SRS (stimulated Raman scattering) is more likely to occur when the linewidth is wide, and LMI (lateral mode instability) is more likely to occur when the optical fiber core mode field diameter is too large [9]. Therefore, a single-mode fiber with a length of 1 m, a mode field diameter of 30 µm, and an attenuation coefficient of 0.4 dB/km are selected [9].…”
Section: Analysis Of Factors Affecting Coherence Of Continuous Fiber ...mentioning
confidence: 99%
See 3 more Smart Citations